A hierarchical routing protocol based on AFSO algorithm for WSN - Xin Song; Cuirong Wang; Juan Wang; Bin Zhang (2010 International Conference On Computer Design and Applications, 2010)
Wireless sensor networks (WSN) will enable the reliable monitoring of a variety environment for both civil and military applications. These networks require robust wireless communication protocols for the purpose of balancing the load and prolonging the network lifetime. In this paper, we propose a novel hierarchical routing protocol based on artificial fish swarm optimization (AFSO). Utilizes AFSO algorithm in cluster formation phase, its main object is to solve the NP-hard problem of finding k optimal clusters according to the given rules. The performance of the novel protocol is compared with the well known cluster-based protocol LEACH and LEACH-C. As the experiment results shown, the protocol can not only improve system lifetime but also prevent the networks form seriously energy consumption.